Review of VSF-Belgium's 'Turkana emergency livestock off-take' intervention 2005 - Watson, D.J.; Binsbergen, J. van (International Livestock Research Institute, 2008)
The 2005 'Turkana Emergency Livestock Off-take' (TELO) intervention contributed to VSFBelgium's overall goal to 'improve the socio-economic status of the pastoral communities living in arid areas of Kenya by creating markets for their livestock and improving the nutritional status of identified target populations'. The six outputs/objectives of the intervention are to increase household income (cash economy) among pastoralists; reduce pressure on water and pasture resources; increase food security for vulnerable school children; improve utilization of assets with livestock owners gaining benefit from vulnerable livestock before the condition of the livestock deteriorates beyond the point of selling; increase access to funds made available to livestock owners for future restocking and; use money saved from the school feeding program for school fees and/or other relevant projects for the pastoralists' school children. Viewed as a significant success, and used as a model for subsequent destocking interventions, it is the aim of this report to evaluate the efficiency and effectiveness of this destocking intervention to highlight both strengths and weaknesses of the approach used and to suggest improvements for future destocking interventions.